1989
DOI: 10.1084/jem.169.1.363
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a cDNA for a new mouse T cell growth factor (P40).

Abstract: Recently, we described a murine helper T cell-derived molecule with T cell growth factor activity that is functionally and structurally distinct from IL-2, IL-4, and other known growth factors. This molecule, designated P40, was identified as a glycoprotein capable of supporting antigen-independent growth of certain helper T cell clones. Here, we report the cloning and expression of a cDNA for this new growth factor. The predicted mature protein is a cationic cysteine-rich polypeptide of 14 kD without signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
60
0
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(64 citation statements)
references
References 17 publications
2
60
0
2
Order By: Relevance
“…Previous studies, largely involving mouse models, have suggested that the common denominator of IL-9 function is to promote the survival of different cell types, including T cells [44] Furthermore, our results indicate that IL-9 treatment maintains, rather than induces, DP T-cell proliferation. These data are in accordance with Houssiau's results [33] indicating that the human T-cell proliferative responses to IL-9 require previous activation.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Previous studies, largely involving mouse models, have suggested that the common denominator of IL-9 function is to promote the survival of different cell types, including T cells [44] Furthermore, our results indicate that IL-9 treatment maintains, rather than induces, DP T-cell proliferation. These data are in accordance with Houssiau's results [33] indicating that the human T-cell proliferative responses to IL-9 require previous activation.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies, largely involving mouse models, have suggested that the common denominator of IL-9 function is to promote the survival of different cell types, including T cells [44], mast cells [35], and eosinophils [45] as well as neurons [46], tumors [47], and epithelial cells [48]. Here, we clearly showed that IL-9 decreased the degree of apoptosis of human intra-tumor DP T cells following growth factor withdrawal.…”
Section: Discussionsupporting
confidence: 56%
“…IL-9 was originally described as a murine T cell growth factor (21). Human and murine IL-9 are 126 amino acids long (21,22).…”
mentioning
confidence: 99%
“…Human and murine IL-9 are 126 amino acids long (21,22). IL-9 is produced by activated T cells and supports the growth of Th clones but not cytolytic clones (23,24).…”
mentioning
confidence: 99%
“…Th9 cells differentiate from naive Th cells in the presence of both TGF-b and IL-4, or from Th2 cells in the presence of TGF-b (6). IL-9 influences many cell types, including T cells, B cells, mast cells, eosinophils, lung epithelial cells, and hematopoietic progenitors (7)(8)(9)(10). The essential roles of IL-9 in the pathogenic progression of type I hypersensitivity have been demonstrated using IL-9-transgenic mice and IL-9-deficient mice.…”
mentioning
confidence: 99%